Amino acid substitution in Cryptococcus neoformans lanosterol 14-α-demethylase involved in fluconazole resistance in clinical isolates - Bosco Borgeat, María E. (2016)
The molecular basis of fluconazole resistance in Cryptococcus neoformans has been poorly studied. A common azole resistance mechanism in Candida species is the acquisition of point mutations in the ERG11 gene encoding the enzyme lanosterol 14-α-demethylase, target of the azole class of drugs. In C. neoformans only two mutations were described in this gene. In order to evaluate other mutations that could be implicated in fluconazole resistance in C. neoformans we studied the genomic sequence of the ERG11 gene in 11 clinical isolates with minimal inhibitory concentration (MIC) values to fluconazole of ≥16 μg/ml. The sequencing revealed the G1855A mutation in 3 isolates, resulting in the enzyme amino acid substitution G484S. These strains were isolated from two fluconazole-treated patients. This mutation would not intervene in the susceptibility to itraconazole and voriconazole.